2018
DOI: 10.15537/smj.2018.8.21394
|View full text |Cite
|
Sign up to set email alerts
|

Circulating rotavirus G and P strains post rotavirus vaccination in Eastern Mediterranean Region

Abstract: Rotavirus circulating strain prevalence in EMR countries has changed post vaccination, and G9P[8], G2P[4], and G9P[4] have become more dominant. Proportion of rotavirus strains in these countries after vaccination has significantly reduced. There is an increase in circulating strain G2P[4] in the post-vaccination period, which needs further monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…In Meghalaya state, 3 strains showed P[8] and 2 showed P[4] genotypes specificity, while, the G genotype was not be typable. These data are consistent with the studies from various countries including Saudi Arabia and Ghana, which indicate that genotype G1P[8] is the most commonly reported and severe diarrhea associated strain followed by G2P[4] and G9P[8] genotypes, respectively (Almalki, 2018;Damanka et al, 2019). In contrast, the proportion of G3 strains (P[8] and P[6]) was significantly higher with the P[8] as the dominant genotype (80.3%) followed by P[6] (14.6%) among patients admitted to the hospital with severe dehydrating diarrhea (Athiyyah et al, 2019) was observed in Indonesia.…”
Section: G and P Genotyping Of Rotavirusessupporting
confidence: 92%
“…In Meghalaya state, 3 strains showed P[8] and 2 showed P[4] genotypes specificity, while, the G genotype was not be typable. These data are consistent with the studies from various countries including Saudi Arabia and Ghana, which indicate that genotype G1P[8] is the most commonly reported and severe diarrhea associated strain followed by G2P[4] and G9P[8] genotypes, respectively (Almalki, 2018;Damanka et al, 2019). In contrast, the proportion of G3 strains (P[8] and P[6]) was significantly higher with the P[8] as the dominant genotype (80.3%) followed by P[6] (14.6%) among patients admitted to the hospital with severe dehydrating diarrhea (Athiyyah et al, 2019) was observed in Indonesia.…”
Section: G and P Genotyping Of Rotavirusessupporting
confidence: 92%
“… 19 reported G1P[4] as the common genotype in sewage isolates in Nigeria. In addition, a previous study in Detroit, MI reported G1P[4] as the dominant circulating strain in children with severe diarrhea, 55 and a review by Almalki and colleagues 63 identified G1P[4] as the dominant strain in Yemen. The emergence of G1P[4] might have resulted from reassortment with G2P[4].…”
Section: Discussionmentioning
confidence: 99%
“…The highest similarity of G2P [4] Moroccan genotypes from vaccinated children with the Italian RVA/ Human-wt/ITA/BERG08/2012/G2P [4] detected in a 14-year old boy, gives interesting information on the circulation of strains in these particular Mediterranean countries during 2012-2014. This genotype is documented to be the major human genotype persisting in >5 years Italian adults [18], while, it has been the major serotype circulating in the post-vaccination era in Morocco (24.4% vs. 15%) or in other Eastern Mediterranean Region [8,19]. The high conservation of VP7 and VP4 genes between either circulating G2P [4] strains in the pre-and post-vaccination periods involve their stability over time.…”
Section: Discussionmentioning
confidence: 97%